All-atom lipid bilayer self-assembly with the AMBER and CHARMM lipid force fields - Skjevik, Åge A. (Chem Commun (Camb), 2015)
This communication reports the first example of spontaneous lipid bilayer formation in unbiased all-atom molecular dynamics (MD) simulations. Using two different lipid force fields we show simulations started from random mixtures of lipids and water in which four different types of phospholipids self-assemble into organized bilayers in under 1 microsecond.